Talcum powder reinforced PC / ABS alloy material and preparation method thereof

By introducing phosphate anhydride compounds into the talc powder-enhanced PC/ABS alloy material, the compatibility between talc powder and PC is improved, and the problems of material toughness are solved and the appearance defects are achieved, and a high-performance and excellent appearance talc powder-enhanced PC/ABS alloy material is achieved.

CN119823554AActive Publication Date: 2025-04-15WANHUA CHEMICAL (NINGBO) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510001942.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-15
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

While the existing talc-enhanced PC/ABS alloy materials have improved rigidity and reduced linear expansion coefficient, their toughness has significantly decreased, and the injection molding appearance has defects such as paint and silver wire.

Method used

By introducing phosphate anhydride compounds, the alkalinity of talc powder is neutralized, the PC resin is protected from degradation, and the terminal hydroxyl group of PC is reacted to improve the compatibility of the inorganic filler talc powder and PC, and the talc powder is better dispersed in the resin.

Benefits of technology

The high impact, high modulus and high heat resistance characteristics of talc powder enhance the high impact, high modulus and high heat resistance of PC/ABS alloy materials, while improving the appearance performance of the material, reducing the defects of the paint and silver wire, and improving the convenience of subsequent processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a talcum powder reinforced PC / ABS alloy material and a preparation method thereof. The composition mainly comprises the following raw materials: polycarbonate resin (PC), acrylonitrile-styrene-butadiene copolymer (ABS), talcum powder and a phosphoric anhydride compound. The phosphoric anhydride compound is prepared by reacting diphenyl phosphine oxide with itaconic anhydride. The obtained talcum powder reinforced PC / ABS alloy material is excellent in appearance and has the characteristics of high impact, high modulus and high heat resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer composite materials, and particularly relates to a talc-reinforced PC / ABS alloy material and a preparation method thereof. Background Art

[0002] In recent years, thin-wall and lightweight have become the development trend of the automotive industry, and PC / ABS alloy, as the most widely used alloy material in this field, has been subject to increasingly diverse requirements from downstream customers. For example, the higher coefficient of linear expansion (CLTE) of PC / ABS will cause parts to be mismatched with other materials when installed, and the tolerance gap will be large or small during the transition from winter to summer, so low-CLTE PC / ABS came into being. Thin-wall requires PC / ABS to have higher rigidity to resist the bending deformation of thin-walled parts.

[0003] Introducing mineral fillers into PC / ABS alloys can increase rigidity and reduce CLTE, thus meeting the above-mentioned thin-wall and lightweight requirements. Glass fiber is a common filler, but it is easy to cause floating fiber when directly applied to PC / ABS alloys, which affects the appearance. At the same time, floating fiber is not conducive to post-processing such as painting and water transfer. Talc is another common filler, which has the advantages of giving the material high rigidity and low CLTE, but the introduction of talc will cause a significant decrease in the toughness of PC / ABS alloys and defects such as material flowers and silver wires in the injection molding appearance. This is because, on the one hand, talc degrades the matrix, and on the other hand, it is difficult to achieve good dispersion of talc in the substrate. Therefore, on the basis of ensuring the high rigidity of talc-filled PC / ABS, how to reduce the toughness loss caused by the introduction of talc is a very meaningful topic.

[0004] In the prior art, CN 116814056 A discloses a mineral-reinforced PC / ABS alloy with good appearance and high performance and a preparation method thereof. However, this method requires the preparation of ABS masterbatch first, which increases production cost and production time.

[0005] Therefore, it is necessary to develop a simple method to prepare talc-reinforced PC / ABS alloy materials with good appearance and high performance. Summary of the invention

[0006] To solve the above problems, the present invention provides a talc-reinforced PC / ABS alloy material and a preparation method thereof. The preparation process of the talc-reinforced PC / ABS alloy material of the present invention is simple and easy, and the prepared alloy material has excellent appearance, high impact, high modulus and high heat resistance.

[0007] In order to achieve the above invention object, the technical solution of the present invention is as follows:

[0008] The present invention provides a talc-reinforced PC / ABS alloy material, which is prepared from the following raw materials in parts by weight:

[0009] Polycarbonate resin (PC) 30-70 parts, preferably 40-60 parts;

[0010] Acrylonitrile-styrene-butadiene copolymer (ABS) 10-50 parts, preferably 20-40 parts;

[0011] 5.0-25 parts of talc, preferably 10-20 parts;

[0012] 0.1-4 parts of phosphoric anhydride compound, preferably 0.5-2 parts;

[0013] Processing aid 0-5 parts, preferably 0.5-3.0 parts;

[0014] Specifically, the polycarbonate resin may be 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, etc.; the acrylonitrile-styrene-butadiene copolymer may be 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, etc.; the talc may be 5 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, etc.; the phosphoric anhydride compound may be 0.1 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, etc.; the processing aid may be 0 parts, 0.1 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, etc.;

[0015] In one embodiment, the phosphoric anhydride compound is prepared by reacting diphenylphosphine oxide with itaconic anhydride in a solvent.

[0016] Specifically, the phosphoric anhydride compound is prepared by the following method, which comprises the following steps:

[0017] Diphenylphosphine oxide, itaconic anhydride and an organic solvent are mixed, stirred for reaction to generate a precipitated product, and then filtered and dried to obtain the phosphoric anhydride compound.

[0018] Preferably, the molar ratio of diphenylphosphine oxide to itaconic anhydride is 1:1-1.5, for example, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, etc.

[0019] Preferably, the organic solvent is selected from one or more of ethyl acetate, methyl acetate, butyl acetate, phenyl acetate, dichloromethane, and diethyl ether, preferably one or more of ethyl acetate and methyl acetate;

[0020] More preferably, the amount of the organic solvent is 1-8 times the mass of diphenylphosphine oxide.

[0021] Preferably, the reaction temperature is not particularly required, for example, the reaction is stirred at room temperature, and the reaction time is 20-45 min, preferably 30-40 min;

[0022] Specifically, the completion of the reaction also includes post-processing operations such as filtration and drying, which are conventional operations in the field and have no special requirements, such as drying in a vacuum drying oven at 100° C. for 4 hours.

[0023] In one embodiment, the polycarbonate resin is selected from one or more of aromatic polycarbonates and aliphatic polycarbonates, preferably bisphenol A polycarbonate;

[0024] Preferably, the polycarbonate resin has a melt flow index of 3-65 g / 10 min, preferably 5-50 g / 10 min, and more preferably 7-35 g / 10 min when tested at 300° C. and 1.2 kg;

[0025] Preferably, the polycarbonate resin is Wanhua 2100 or Wanhua 2150.

[0026] In one embodiment, the acrylonitrile-styrene-butadiene copolymer, wherein the mass content of butadiene is 10-30%, the mass content of acrylonitrile is 15-35%, and the mass content of styrene is 50-70%;

[0027] Preferably, the acrylonitrile-styrene-butadiene copolymer is Chimei PA-757 or Chimei PA-747.

[0028] In one embodiment, the talc powder has a particle size of 1-9 μm;

[0029] Preferably, the talc powder is Yiruishi R7 or Yiruishi 3CA.

[0030] In one embodiment, the processing aid is selected from one or more combinations of antioxidants, lubricants, toughening agents, ultraviolet absorbers, compatibilizers, light stabilizers, heat stabilizers, metal passivators, plasticizers, anti-adhesive agents, colorants, coupling agents, nucleating agents, foaming agents, antibacterial agents, mildew inhibitors, acid scavengers, hydrolysis resistance agents, chain extenders, flow modifiers, matting agents, antistatic agents, reinforcing agents, fillers, antifogging agents, light diffusers, infrared absorbers, fluorescent brighteners and laser marking agents, preferably one or more of antioxidants, lubricants and toughening agents; preferably, based on 0-5 parts of processing aids, their respective amounts are: 0-0.5 parts of antioxidants, 0-1 parts of lubricants, and 0-4 parts of toughening agents.

[0031] Preferably, the antioxidant is selected from one or more of hindered phenols, phosphites, thioesters, benzofurans, acryl-modified phenols, and hydroxylamine antioxidants, more preferably one or more of BASF antioxidants Irganox 1076, Irganox 1010, Irganox 168, Irgafos 126, Irgafos P-EPQ, and Irganox B900;

[0032] Preferably, the lubricant is selected from one or more of fatty alcohols, fatty acids, fatty acid esters, montan waxes, amide waxes, saturated hydrocarbons, silicones and polysiloxanes, preferably pentaerythritol stearate;

[0033] Preferably, the toughening agent is selected from one or more of methyl methacrylate-butadiene-styrene copolymer, methyl methacrylate-acrylic polymer, acrylic acid-silicone rubber toughening agent, ethylene-methyl acrylate, ethylene-butyl acrylate, ethylene-acrylate-glycidyl methacrylate terpolymer, preferably one or more of methyl methacrylate-butadiene-styrene copolymer, more preferably one or more of EM500 and M711.

[0034] Adding certain additives to PC materials is a conventional technical means in the field. Technicians can selectively use the above additives according to product performance characteristics. The present invention has no special requirements on the specific type and amount of the additives, and corresponding adjustments can be made based on existing technologies according to needs.

[0035] The present invention also provides a method for preparing the talc-reinforced PC / ABS alloy material, which is prepared by adding various raw materials into a twin-screw extruder for melt extrusion and granulation, which is a conventional method in the art and has no special restrictions.

[0036] For example, an exemplary preparation method comprises the following steps:

[0037] Polycarbonate resin, acrylonitrile-styrene-butadiene copolymer, phosphoric anhydride compound and processing aid are mixed according to the formula ratio, and fed into the main feeding port of the twin-screw extruder. At the same time, talcum powder is fed into the side feeding port, and then melt-extruded and granulated to obtain talcum powder reinforced PC / ABS alloy material.

[0038] Preferably, the temperature of the conveying section of the twin-screw extruder is set to 210-220°C, the temperature of the plasticizing section is set to 225-270°C, the temperature of the metering section is set to 225-260°C; and the screw speed is 200-600rpm.

[0039] The talc-reinforced PC / ABS alloy material of the present invention can be widely used in the fields of automobiles, electronic appliances, etc., and is particularly suitable for applications such as automobile spoilers and integrated front faces.

[0040] The beneficial effects of the present invention are:

[0041] The present invention introduces phosphoric anhydride compounds into the talc-reinforced PC / ABS alloy material, and the phosphoric anhydride compounds can neutralize the alkalinity of the talc and protect the PC resin from degradation. At the same time, the phosphoric anhydride compounds have a part of epoxy functional groups, which can react with the terminal hydroxyl groups of PC, greatly improve the compatibility of the inorganic filler talc and PC, and help the talc to be better dispersed in the resin. The talc-reinforced PC / ABS alloy material of the present invention has good mechanical properties and excellent appearance properties, and the phosphoric anhydride compounds have the effect of reducing the internal stress of the material, which is beneficial to subsequent processing procedures such as painting and water transfer printing. DETAILED DESCRIPTION

[0042] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.

[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs. Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially.

[0044] The main raw material sources are as follows:

[0045] Polycarbonate resin (PC): Bisphenol A polycarbonate produced by interfacial phosgene method, Clarnate 2150, melt flow index of 15 g / 10 min (300 ° C, 1.2 kg); Clarnate 2100, melt flow index of 10 g / 10 min (300 ° C, 1.2 kg); Wanhua Chemical Group Co., Ltd.

[0046] ABS resin: ABS particles produced by blending method, PA-757, melt flow index is 19g / 10min (220℃, 10kg); PA-747, melt flow index is 12g / 10min (220℃, 10kg); Chi Mei Industrial;

[0047] Talc: R7, D50 is 2μm; 3CA, D50 is 6μm; Yiruishi Company;

[0048] Antioxidant: Irganox B900, BASF;

[0049] Lubricant: GLYCOLUBE PETS, pentaerythritol stearate, Lonza, USA;

[0050] Toughening agent: EM500, produced by LG, South Korea; M711, produced by Kaneki, Japan;

[0051] Diphenylphosphine oxide: Sinopharm Chemical Reagent Co., Ltd.;

[0052] Itaconic anhydride: Sinopharm Chemical Reagent Co., Ltd.;

[0053] 1-Propylphosphonic anhydride: Sinopharm Chemical Reagent Co., Ltd.

[0054] Preparation Example 1-3:

[0055] Phosphoric anhydride compound 1: Add 50 g (0.247 mol) of diphenylphosphine oxide and 28 g (0.250 mol) of itaconic anhydride to 300 g of ethyl acetate, stir and react at room temperature for 30 min to obtain a precipitated product, filter and separate the insoluble matter, and dry it in a vacuum drying oven at 100°C for 4 h to obtain phosphoric anhydride compound 1.

[0056] Phosphoric anhydride compound 2: Add 50 g (0.247 mol) of diphenylphosphine oxide and 35 g (0.312 mol) of itaconic anhydride to 350 g of ethyl acetate, stir and react at room temperature for 30 min to obtain a precipitated product, filter and separate the insoluble matter, and dry it in a vacuum drying oven at 100°C for 4 h to obtain phosphoric anhydride compound 2.

[0057] Phosphoric anhydride compound 3: Add 50 g (0.247 mol) of diphenylphosphine oxide and 40 g (0.357 mol) of itaconic anhydride to 400 g of ethyl acetate, stir and react at room temperature for 30 min to obtain a precipitated product, filter and separate the insoluble matter, and dry it in a vacuum drying oven at 100°C for 4 h to obtain phosphoric anhydride compound 3.

[0058] Examples 1-4

[0059] Polycarbonate resin (PC), acrylonitrile-styrene-butadiene copolymer (ABS), phosphoric anhydride compounds, antioxidants, lubricants, and toughening agents were mixed according to the raw material types and masses (unit / Kg) in Table 1, and fed into the main feeding port of a twin-screw extruder, and talcum powder was fed into the side feeding port, and then melt-extruded, wherein the temperature of the conveying section of the twin-screw extruder was set to 210° C., the temperature of the plasticizing section was set to 240° C., the temperature of the metering section was set to 230° C., the screw speed was 400 rpm, and granulation was performed to obtain a talcum powder reinforced PC / ABS alloy material.

[0060] Comparative Examples 1-4

[0061] The talc-reinforced PC / ABS alloy materials in Comparative Examples 1-4 were prepared respectively according to the method basically the same as that in Example 1, except that the types and proportions of raw materials were adjusted according to Table 1 (unit / Kg), and other parameters and operating conditions remained unchanged.

[0062] Table 1 Comparative Examples 1-4 and Examples 1-4 Formula

[0063]

[0064] The talc-reinforced PC / ABS alloy materials in Examples 1-4 and Comparative Examples 1-4 were tested for their properties according to the following method. The results are shown in Table 2:

[0065] Main test methods

[0066] The notched impact strength is tested according to ISO 179 standard, with specimen size: 80*10*4mm and notch depth 2.0mm.

[0067] The heat deformation temperature (HDT) was tested according to ISO 75 standard with a load of 1.80 MPa and a heating rate of 120°C / h.

[0068] The tensile strength was tested according to ISO 527, with a specimen size of 170*10*4mm and a rate of 50mm / min.

[0069] The tensile modulus was tested according to ISO 527, with a specimen size of 170*10*4 mm and a rate of 1 mm / min.

[0070] The appearance evaluation is carried out by injection molding large highlight boards to evaluate defects such as material spots and silver threads. The size of the large highlight board (mm) is: 300*150*3, where "-" represents no defects such as material spots and silver threads, and the more "+"s there are, the more defects such as material spots and silver threads there are.

[0071] Table 2 Performance test results of the products obtained from Comparative Examples 1-4 and Examples 1-4

[0072]

[0073] By comparing Examples 1-4 and Comparative Examples 1-4, when diphenylphosphine oxide is added alone, itaconic anhydride is added alone, 1-propyl phosphoric anhydride is added alone, or diphenylphosphine oxide and itaconic anhydride are added simultaneously, the resulting composition has a low notched impact strength, and the injection molding appearance has many defects such as material flowers and silver wires. After adding phosphoric anhydride compounds, the impact properties of the material can be greatly improved, and the injection molding appearance is also significantly improved. Even at a high addition amount of 25% of talc, the impact can be maintained at 30KJ / m 2The above results show that the phosphoric anhydride compounds have good tensile strength, tensile modulus and thermal deformation properties, which indicates that the phosphoric anhydride compounds greatly improve the compatibility of talc and PC and greatly reduce the degradation of talc to PC.

[0074] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.

Claims

1. A talc-reinforced PC / ABS alloy material, characterized in that: Prepared from the following raw materials in parts by weight: 30-70 parts of polycarbonate resin, preferably 40-60 parts; 10-50 parts of acrylonitrile-styrene-butadiene copolymer, preferably 20-40 parts; 5.0-25 parts of talc, preferably 10-20 parts; 0.1-4 parts of phosphoric anhydride compound, preferably 0.5-2 parts; Processing aid 0-5 parts, preferably 0.5-3.0 parts; The phosphoric anhydride compound is prepared by reacting diphenylphosphine oxide with itaconic anhydride in a solvent.

2. The talc-reinforced PC / ABS alloy material according to claim 1, characterized in that: The phosphoric anhydride compound is prepared by the following method, which comprises the following steps: Diphenylphosphine oxide, itaconic anhydride and an organic solvent are mixed, stirred for reaction to generate a precipitated product, and then filtered and dried to obtain the phosphoric anhydride compound.

3. The talc-reinforced PC / ABS alloy material according to claim 1 or 2, characterized in that: The molar ratio of diphenylphosphine oxide to itaconic anhydride is 1:1-1.5; and / or The organic solvent is selected from one or more of ethyl acetate, methyl acetate, butyl acetate, phenyl acetate, dichloromethane, and ether, preferably one or more of ethyl acetate and methyl acetate; and / or The amount of the organic solvent is 1-8 times the mass of diphenylphosphine oxide; and / or The reaction time is 20-45 min, preferably 30-40 min.

4. The talc-reinforced PC / ABS alloy material according to claim 1, characterized in that: The polycarbonate resin is selected from one or more of aromatic polycarbonate and aliphatic polycarbonate, preferably bisphenol A polycarbonate; Preferably, the polycarbonate resin has a melt flow index of 3-65 g / 10 min, preferably 5-50 g / 10 min, and more preferably 7-35 g / 10 min when tested at 300° C. and 1.2 kg; Preferably, the polycarbonate resin is one or more of Wanhua 2100 and Wanhua 2150.

5. The talc-reinforced PC / ABS alloy material according to claim 1, characterized in that: The acrylonitrile-styrene-butadiene copolymer, wherein the mass content of butadiene is 10-30%, the mass content of acrylonitrile is 15-35%, and the mass content of styrene is 50-70%; Preferably, the acrylonitrile-styrene-butadiene copolymer is one or more of Chimei PA-757 and Chimei PA-747.

6. The talc-reinforced PC / ABS alloy material according to claim 1, characterized in that: The talcum powder has a particle size of 1-9 μm; Preferably, the talc powder is one or more of Yiruishi R7 and Yiruishi 3CA.

7. The talc-reinforced PC / ABS alloy material according to claim 1, characterized in that: The processing aid is selected from one or more combinations of antioxidants, lubricants, toughening agents, ultraviolet absorbers, compatibilizers, light stabilizers, heat stabilizers, metal passivators, plasticizers, anti-adhesive agents, colorants, coupling agents, nucleating agents, foaming agents, antibacterial agents, mildew inhibitors, acid scavengers, hydrolysis resistant agents, chain extenders, flow modifiers, matting agents, antistatic agents, reinforcing agents, fillers, antifogging agents, light diffusers, infrared absorbers, fluorescent brighteners and laser marking agents, preferably one or more of antioxidants, lubricants and toughening agents.

8. The talc-reinforced PC / ABS alloy material according to claim 1, characterized in that: Based on 0-5 parts of processing aid, the respective amounts are 0-0.5 parts of antioxidant, 0-1 parts of lubricant, and 0-4 parts of toughening agent; and / or The antioxidant is selected from one or more of hindered phenols, phosphites, thioesters, benzofurans, acryl-modified phenols, and hydroxylamine antioxidants, preferably one or more of BASF antioxidants Irganox 1076, Irganox 1010, Irganox 168, Irgafos 126, Irgafos P-EPQ, and Irganox B900; and / or The lubricant is selected from one or more of fatty alcohols, fatty acids, fatty acid esters, montan waxes, amide waxes, saturated hydrocarbons, organosilicones and polysiloxanes, preferably pentaerythritol stearate; and / or The toughening agent is selected from one or more of methyl methacrylate-butadiene-styrene copolymer, methyl methacrylate-acrylic polymer, acrylic acid-silicone rubber toughening agent, ethylene-methyl acrylate, ethylene-butyl acrylate, ethylene-acrylate-glycidyl methacrylate terpolymer, preferably one or more of methyl methacrylate-butadiene-styrene copolymer, more preferably one or more of EM500 and M711.

9. The method for preparing a talc-reinforced PC / ABS alloy material according to any one of claims 1 to 8, characterized in that: Here are the steps: Polycarbonate resin, acrylonitrile-styrene-butadiene copolymer, phosphoric anhydride compound and processing aid are mixed according to the formula ratio, and fed into the main feeding port of the twin-screw extruder. At the same time, talcum powder is fed into the side feeding port, and then melt-extruded and granulated to obtain talcum powder reinforced PC / ABS alloy material.

10. The preparation method according to claim 9, characterized in that: The temperature of the conveying section of the twin-screw extruder is set to 210-220° C., the temperature of the plasticizing section is set to 225-270° C., and the temperature of the metering section is set to 225-260° C.; the screw speed is 200-600 rpm.

Citation Information

Patent Citations

  • Hyperbranched flame-retardant epoxy resin and epoxy resin composition prepared from same

    CN115894860A

  • Application of phosphorus-containing anhydride compound in epoxy resin adhesive

    CN116751357A

  • Talcum powder filled PC / ABS alloy material as well as preparation method and application thereof

    CN117700973A

  • Preparation method of liquid phosphorus-containing anhydride curing agent

    CN118725257A